Incorporating Arabic words in the teaching of English to Muslim learners: students' perspectives - Othman, Khairiah; Mohammad Lotfie, Maskanah Mohammad (2010)
The presence of many words and concepts in the English language that do not correspond to the meaning held by Muslims has been highlighted by many Muslim scholars (al-Attas, 1993; al-Faruqi ,1986; Haja Mohideen, 2001, Ratnawati, 1996). Al-Faruqi (1986), for instance, argues that not only many English words do not convey the necessary meanings, but also more importantly, they are unable to convey the meanings that Muslims intend to convey due to the fact that many Arabic words are not translatable into English. To him, many of the meanings of Arabic words and phrases are of divine provenance and may not be separated from their Arabic forms. Hence, he proposes the use of Islamic vocabulary be retained in their Arabic form in an effort to maintain the original meanings. In this paper, postgraduate students’ perspectives were sought as to whether there is a need for Islamic Arabic vocabulary to be incorporated in the teaching of English to Muslim learners. This paper will explore pedagogical implications to ESL teachers who teach English to Muslim learners.